Enhancement of Tourism Promotion Efforts in DKI Jakarta - Taufiq Rachman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study discusses about enhancement of tourism promotion efforts in DKI Jakarta. Variables in the study consists of security stability variables and macroeconomic policies, tourism policies and budgets, tourism development strategies, strategies for supporting facilities and infrastructure development, length of stay improvement programs for foreign tourist visits, increased tourist visits to the archipelago, tourism sector MSMEs development, creation Tourism Employment, and Regional Revenue Increase from the Tourism Sector. The object of research is tourism businesses and MSMEs that carry out tourism sector activities in DKI Jakarta. Whereas the subjects in this study were leaders / managers, and MSMEs entrepreneurs, as well as other related parties. The result shows that there is a meaningful relationship between the variables of Security Stability and Macroeconomic Policy, Tourism Policy and Budget, Tourism Object Development Strategy, Tourism Support Facilities and Infrastructure Development Strategy, Length of Stay Program. The lowest closeness of the relationship is the Security Stability and Macroeconomic Policy variables with the Tourism Object Development Strategy variable, while the highest relationship closeness is the Security and Macroeconomic Policy variables, the Policy with the Length of Stay Program Improvement variable.